Influência da gipsita no surgimento de eflorescência em telhas cerâmicas - Monteiro, Celina Margarida de Oliveira Lima (2009)
The red ceramic industry is recognized as of major importance in Piauí State. The State capital, Teresina, is the greatest producer of this material ( production about 18 million peaces), which is used mainly for masonry sealing blocks. One of the most frequent problems in this kind of products is the efflorescence. This work has the main objective of studying the influence of gypsum addition on non-glazed tiles, by using the local industry production standards. The raw materials were characterized by FRX, DRX, TGA, DTA and AD. Extruded test specimens were made with the addition of 1, 3 and 5% of gypsum in the ceramic paste, burned at 850oC, 950oC and 1050oC and submitted to further technological tests and microestrutural analysis by the scanning electron microscope. In order to accelerate the aging of bodies of evidence, they were immersed in successive water baths and posterior drying. The reference ceramic paste showed tendency to efflorescence formation after drying and consolidated efflorescence after burning, but no affecting the technological results